STATUS ORAL HIGIENE DAN KARIES GIGI PADA VEGETARIAN DAN NON VEGETARIAN DI MAHA VIHARA MAITREYA MEDAN: ORAL HYGIENE AND CARIES STATUS ON VEGETARIAN AND NON VEGETARIAN MAITREYA GREAT TEMPLE MEDAN - Simson Damanik; Albert Prawira (TALENTA, 2010)
Different eating patterns between vegetarians and non vegetarians may affect oral and dental health. The aim of this study was to know the difference of oral hygiene and dental caries condition between vegetarians and non vegetarians at Maha Vihara Maitreya Medan. The design of study was cross sectional study. Samples consisted of 74 vegetarians and 65 non vegetarians. Oral hygiene measurement used OHIS index from Greene and Vermillion. Dental caries measurement used DMFT index from Klein, where as data about eating patterns were obtained from respondents by using questionnaire. The results showed that the mean OHIS score for vegetarian group was 2.20, as for non vegetarian group was 2.52. The mean DMFT score for vegetarian group was 5.78, as for non vegetarian group was 7.02. The eating patterns of carbohydrate source foods, vegetables and fruits were almost identical between vegetarians and non vegetarians, the difference was on the protein source food consumption. The most protein source which was consumed by vegetarians was soybean and its refined product, where as for non vegetarians ware meat. As conclusion, there were significant differences about oral hygiene and dental caries condition between vegetarians and non vegetarians.